Management implications of new research on problem elephants - Richard Hoare (Pachyderm)
The persistance of problem elephant behaviour appears to continue, at least in some populations, even when identified culprit individuals are routinely removed from these populations over a long time. Is it possible that elephant populations, rather than having a few habitual problem animals, may have what could be termed a problem component? Neither translocation or killing of problem animals appears to work, others simply take their place. This implies that in such populations either translocation or killling of problem anaimls will have to continue indefinately. Although difficult to test this reasoning is supported by considerable circumstantial evidence and agrees with accepted principles in agricultural pest cntrol. Merely killing (removing) individuals of the pest species seldom has much impact of the problem, most pests are effectively controlled by denying them their target food or a nearby refuge.